Goethes Liebeslyrik : Semantiken der Leidenschaft um 1800. - Valk, Thorsten (Klassik und Moderne., 2013)
Goethe's lyrical works had a major impact upon the emergence of the modern discourse of love. Along with the texts of his creative period in Weimar, the poems of his Leipzig, Strasbourg, and Frankfurt years represent an ever-changing poetics of love that competed with contemporary perspectives from the Enlightenment to Late Romanticism. Goethe's formal innovations over the course of his love poetry, often accompanied by intercultural references, have proven to be singular.